HINT1 Is Involved in the Chronic Mild Stress Elicited Oxidative Stress and Apoptosis Through the PKC ε/ALDH-2/4HNE Pathway in Prefrontal Cortex of Rats - Liu, Fei; Dong, Ying-ying; Lei, Gang; Zhou, Yuan; Liu, Peng; Dang, Yong-hui (Frontiers in Behavioral Neuroscience, 2021)
Major depressive disorder is a severe, highly heterogeneous and life-threatening psychiatric disease which affects up to 21% of the population worldwide. A new hypothesis suggests that the mitochondrial dysfunction causing oxidative stress (OS) and dysregulation of apoptosis in brain might be one of the key pathophysiological factors in major depressive disorder. Histidine triad nucleotide binding protein 1 (HINT1), which was first supposed to be protein kinase C (PKC) inhibitor, has been gradually demonstrated to be involved in diverse neuropsychiatric diseases. It still remains elusive that how HINT1 involves in depression. The present study utilized a rat model exposed to chronic mild stress (CMS) to explore the involvement of HINT1 in depression. Face validity, construct validity and predictive validity of CMS model were comprehensive evaluated in this study. Behavioral tests including sucrose preference test, open field test, elevated plus maze and forced swimming test revealed that stressed rats displayed elevated level of anxiety and depression compared with the controls. CMS rats showed a significant decrease of superoxide dismutase, and a marked increase malondialdehyde levels in prefrontal cortex (PFC). We also found the CMS rats had elevated expression of HINT1, decreased levels of phosphorylated-PKC ε and aldehyde dehydrogenase-two (ALDH-2), and accumulated 4-hydroxynonenal (4HNE) in PFC. Moreover, CMS increased the levels of Cleaved Caspase-3 and Bax, and decreased the level of Bcl-2 in PFC. The alterations in behavior and molecule were prevented by antidepressant venlafaxine. These results demonstrated that HINT1 was involved in the CMS elicited OS and apoptosis in PFC, probably through the PKC ε/ALDH-2/4HNE pathway. The results suggest that the suppression of HINT1 might have potential as a novel therapeutic strategy for depression.